Advanced hybrid optimization methods for the design of complex separation processes. (April 2021) - Kruber, Kai Fabian; Grueters, Tamara; Skiborowski, Mirko
Highlights: Evaluation of two advanced hybrid optimization methods for MINLP problems. Global optimization for simple column design verified by comparison with BARON. EA-based hybrid algorithm more efficient than MSGS-based hybrid algorithm. Optimization-based design of energy-integrated process and solvent selection. Illustration for extractive distillation process for acetone-methanol separation. Abstract: While the need for more efficient and integrated processes for the separation of non-ideal and azeotropic mixtures mandates model-based design methods, the resulting mixed-integer problems are highly nonlinear and particularly hard to solve without proper initialization. In order to handle such complex design problems, two hybrid optimization methods are presented in the current contribution. Both methods rely on a nested approach, which integrates a polylithic modeling and solution strategy, based on the solution of successively refined nonlinear programming problems, with an upper level metaheuristic for the initialization and optimization of discrete design decisions. Both methods are evaluated for two case studies. The optimization of a simple column design problem allows for the direct comparison with an available global deterministic optimization solver for identifying the global optimal solution. The optimization of an extractive distillation process with simultaneous solvent selection and energy integration illustrates the potential complexity that can be handled effectively.